Clinical, pharmacotherapeutic and nutritional characterization of patients with Diabetes Mellitus (Research, Society and Development, 2021)
Diabetes is a genetic and hereditary disease, considered a syndrome of metabolism that results in the accumulation of glucose by the body. Diabetes treatment aims to prevent and cure possible complications and maintain quality of life. The aim of this study is to characterize patients with diabetes mellitus regarding nutritional and clinical factors, the pharmacotherapy used. A target audience of patients over 15 years old, diagnosed with type I and II diabetes was chosen. A questionnaire was applied to identify the variables related to the type of treatment performed by the patient (medicated and non-medicated). In addition, the age group, income, education, marital status and clinical variables (time of diagnosis, comorbidities, chronic complications), anthropometric, adherence to drug treatment and Frequency of Food Consumption were analyzed. This study found a greater number of female patients, aged over 60 years. A high number of patients reported physical inactivity, thus leading to an increase in sedentary lifestyle and waist circumference. The sample population does not fully adhere to the recommended methods for diabetes control, as most of the patients interviewed do not do due nutritional monitoring and do not have the habit of regular physical exercise. In addition, part of the studied population is not adherent to drug treatment.